PENGARUH PEMBERIAN ENERGI, KARBOHIDRAT, PROTEIN, LEMAK TERHADAP STATUS GIZI DAN KETERAMPILAN ATLET SEPAK BOLA - Ramadhani, Renjani Gina; Murbawani, Etisa Adi (Departemen Ilmu Gizi, Fakultas Kedokteran, Universitas Diponegoro, 2012)
Background: Good skills in soccer are very needed to accomplish the achievement. Nutritional status in soccer athletes can effect the performance on the match. Besides exercises, nutrition intake is considered to have an effect on the nutritional status and skills of soccer athletes. Objective: The purpose of this study was to determine the effect of food intake on nutritional status and skills of soccer athletes. Methods: An experimental study with one group pre and post test designed on soccer athletes in PPLP Central Java on June 2012. Food intake were given in 55%-60% carbohydrates, 15%-20% protein, 20%-30% fat. Anthropometry, physical fitness, skill (passing and dribbling), and nutrition intake were measured pre- and post- intervention. The data obtained were analyzed by paired t-test and Pearson correlation. Results: Eighteen subjects completed this study. Significant increase in energy intake (p= 0,000), carbohydrate (p= 0,000), protein (p= 0,000), fat (p= 0,000), BMI (p= 0,000), percent body fat (p= 0,031), physical fitness (p= 0,038), and passing (p= 0,000), but no significant differences found on dribbling (p= 0,056) after a given intervention. There was no effect of energy, carbohydrate, protein, fat on nutritional status and skills of soccer athletes (p> 0.05). Conclusion: There was no effect of energy, carbohydrate, protein, fat on nutritional status and skills of soccer athletes.